Ta’limu al-Mahārat al-Qur'āniyyah - Ahmad Suyuti Anshori (Al-Jami'ah Research Centre, 2004)
The qur'an is the great miracle of the prophet Muhammad saw. The book is absolutely holy, far from any distortion as underwent by other holy books. The Qur'an book is the most authentic source book ever given to human civilization. Nowadays no scholars or linguist could imitate the beauty and then compact quality of the Qur’an. In addition, the Qur’an has also made a significant contribution to Arabic language and also its eternity. Thanks to the book, the Arabs became one community, and Muslims could unearth on knowledge. Therefore, the Qur’an has become the central point for Muslims from the time of the Prophet to our recent area. A number of religious scholars, researchers, and writers have focused their attention on the holy book, from way how to read, write, memories, interpret, and study its miracle. This writing elaborates on the way how to teach skill about the Qur'an i.e., listening, writing, reading, and memorizing-all in relation to various theories of education.